Education Financing Planning Strategy at Yppk Santo Petrus Ayawasi Elementary School - Taa, Apolos; Sumual, Shelty D. M. (JUPE : Jurnal Pendidikan Mandala, 2024)
This research aims to identify and formulate effective education financing planning strategies at YPPK Santo Petrus Ayawasi Elementary School through a literature review. The findings were obtained from analysis of relevant literature, which includes identification of financing needs, sources of financing, and management and use of education funds. From the results of the analysis, it was found that SD YPPK Santo Petrus Ayawasi needed infrastructure improvements, development of teaching staff, and extracurricular programs as priorities in planning education financing. Diversification of funding sources from the government, community and private sector is needed to increase school financial stability. Effective fund management through performance-based budgeting, transparency, and the use of information technology are also keys to a successful education financing planning strategy. Based on these findings, the recommendations given to SD YPPK Santo Petrus Ayawasi include conducting routine needs analysis, increasing diversification of funding sources, implementing a school management information system (SIMS), and strengthening transparency and accountability in fund management. It is hoped that these strategies can help schools optimize education financing planning and improve the quality of education provided to students.